2014
DOI: 10.1093/jac/dku164
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable increase in fluoroquinolone-resistant Mycoplasma genitalium in Japan

Abstract: Macrolide- or fluoroquinolone-resistant M. genitalium appears to be increasing, and the increase in fluoroquinolone-resistant mycoplasmas is especially remarkable in Japan. Mycoplasmas harbouring 23S rRNA mutations would be resistant to the AZM-SR regimen, but those harbouring ParC alterations would still be susceptible to the sitafloxacin regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
104
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 30 publications
11
104
2
2
Order By: Relevance
“…The high frequency of resistance and the limited treatment options necessitate rapid resistance assays to spare secondary treatment options (6). Indeed, emerging resistance to secondary treatment options using fluoroquinolones has already been reported in selected populations (3,4,8,17).…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of resistance and the limited treatment options necessitate rapid resistance assays to spare secondary treatment options (6). Indeed, emerging resistance to secondary treatment options using fluoroquinolones has already been reported in selected populations (3,4,8,17).…”
Section: Discussionmentioning
confidence: 99%
“…21 Recently, we have reported the emergence and increase of MG clinical strains harboring mutations in the 23S rRNA gene associated with macrolide resistance and/or those in the parC gene associated with fluoroquinolone resistance. 29 The single-dose regimen of azithromycin 1 g or extended-release azithromycin 2 g failed to eradicate MG strains with the mutant 23S rRNA gene in some cases of NGU, but the regimen of sitafloxacin 100 mg twice daily for 7 days was still effective on NGU caused by MG strains with the mutant parC gene. 29 In addition, sitafloxacin has been reported to be highly active against HI.…”
mentioning
confidence: 97%
“…29 The single-dose regimen of azithromycin 1 g or extended-release azithromycin 2 g failed to eradicate MG strains with the mutant 23S rRNA gene in some cases of NGU, but the regimen of sitafloxacin 100 mg twice daily for 7 days was still effective on NGU caused by MG strains with the mutant parC gene. 29 In addition, sitafloxacin has been reported to be highly active against HI.…”
mentioning
confidence: 97%
“…Kikuchi et al [69] from Japan reported that in 27 MG specimens in 2011 and in 24 in 2012, no macrolide resistance-associated mutations in the Moreover, three isolates in 2013 coincidentally carried both antibiotic resistance-associated phenotypes. As the case of macrolide resistance with 23S rRNA mutations, fluoroquinolone resistance in MG is frequently associated with the mutations of the molecular target genes in MG. During prokaryotic DNA replication and transcription, DNA strands are subjected to various conformational stresses.…”
Section: ) Topoisomerase Iiamentioning
confidence: 99%
“…The antibacterial activities of the quinolones may be due to their inhibitory activities against bacterial type II topoisomerases, such as DNA gyrase and topoisomerase IV (Table 6) [54,[67][68][69]71,72]. Therefore, it has been reported that mutations in the quinolone resistance-determining regions of the type II topoisomerases contribute to quinolone resistance in various bacterial species, including MG [67][68][69].…”
Section: ) Topoisomerase Iiamentioning
confidence: 99%